Overview of Completeness of Filling Out Inpatient Discharge Summary Form at General Ahmad Yani General Hospital Metro in 2021 - Aulia, Ni Wayan Riskita; Wiwik Viatiningsih; Nanda Aula Rumana; Puteri Fannya (HM Publisher, 2022)
Medical records are the property of hospitals that must be maintained because they are useful for patients, doctors, and hospitals. Medical record documents are very important in carrying out the quality of medical services provided by hospitals and their medical as well as accurate evidence in court, doctors, nurses, and other health workers who treat patients are required to complete medical records following applicable regulations. This study aims to describe the completeness of filling out inpatient discharge summary form at General Ahmad Yani Hospital Metro in 2021. This study used a descriptive research method. The research location is the Medical Record Unit of General Ahmad Yani General Hospital Metro Lampung. This research was conducted in October 2021. Of the 100 samples of medical records, the completeness of the inpatient discharge summary form was completed. There are 80% complete and 20% incomplete, where the completeness value of 100% is found in the patient identity filling item, and there are no scribbles. Meanwhile, 20% incompleteness is found in important note items (5%) and authentication (15%). In conclusion, standard operating procedures for completeness of medical records already exist and the implementation of completeness of medical record files has been carried out according to applicable standards, but it can be seen that the steps in the SOP are not detailed and less thorough.